The impact of human age on the amount of absorbed energy from mobile phone. Issue 5 (24th July 2019) - Jovanovic, Dejan B.; Stankovic, Vladimir; Cvetkovic, Nenad N.; Krstic, Dejan; Vuckovic, Dragan
Abstract : Purpose: The purpose of this paper is to determine the impact of human age on the distribution of electric field and absorbed energy that originates from a mobile phone. Design/methodology/approach: This research was performed for frequencies of 900, 1800 and 2100 MHz, which are used in a mobile communication system. To obtain the most accurate results, 3 D realistic model of the child's head has been created whereby the dimensions of this model correspond to the dimensions of a seven-year-old child. Distribution of the electric field and specific absorption rate (SAR) through the child's head was obtained by numerical analysis based on the finite integration technique. Findings: The results discover that amount of absorbed energy is greater in the surface layers of the child's head model when the electromagnetic (EM) characteristics of tissues are adjusted for the child. This deviation corresponds to different EM characteristics of biological tissues and organs of an adult person compared to a child. Research limitations/implications: The study deals with penetrated electrical field and absorbed EM field energy. There is space for further studies of other EM field effects (e.g. thermal effects). Practical implications: The analysis of obtained results leads to idea that mobile phones and devices aimed for children using should be modified to provide SAR values inside prescribed standards. Social implications: The obtained results are foundation for future research on influence of EM fields of mobile devices on human health. Originality/value: The proposed procedure offers the model for accurate estimation and quality analysis of SAR and EM field distribution inside child head tissue.